(In)Definitud e (in)especificidad de los grupos nominales. Un caso de antecedente expreso - Pawlik, Janusz (Neophilologica, 2019)
The definite and indefinite articles have been studied by scholars from different backgrounds and perspectives. In this paper we take a close insight into basic terms such as definiteness—indefiniteness, specificity—non-specificity. The paper is also concerned with the (in)definite reference of a noun phrase which is the head of a relative clause in Spanish. Speakers and hearers do not share any knowledge of the referent on the basis of previously mentioned (anaphora) or situational uses. There is something about the relative clause that makes a first-mention definite article possible. We take an insight into the contents of the description conveyed by such relatives.